Non-stereotactic radiotherapy in older cancer patients. Issue 6 (June 2022) - Parisi, Silvana; Lillo, Sara; Cacciola, Alberto; Ferini, Gianluca; Valenti, Vito; Viola, Anna; Santacaterina, Anna; Platania, Angelo; Brogna, Anna; Tamburella, Consuelo; Pergolizzi, Stefano
Abstract: Old or very old oncological patients represent a heterogeneous and frail population due to concomitant comorbidities. Whether radiotherapy alone or in combination with novel cancer drugs may provide a clear benefit in this setting of patients is still a matter of debate. The aim of our review is to analyze the evaluation process and the different therapeutic possibilities in older cancer patients, focusing on the different and most disparate applications of radiotherapy. We reviewed the most recent literature on radiotherapy in older patients providing clinical evidence of treatment related toxicity, tolerance and outcomes using standard fractionated and/or hypofractionated irradiation alone or in combination with chemotherapy, targeted and immunotherapy. In older cancer patients unfit for systemic therapy or surgery, radiotherapy represents a valid therapeutic approach, both with curative and palliative intents, ensuring excellent patient compliance in terms of local toxicity and adherence to therapy. Abstract : Frailty; Geriatrics; Radiation oncology.